ANALISA STRATEGY PEMASARAN DAN DISTRIBUSI PRODUK BABY DIAPERS MERK SWEETY DI REGION SULAWESI - Nasrum Nasir (Scientia Integritas Utama, 2023)
In today's era, human activities are very busy, so every individual wants things to be more practical, including for the needs of everyday life. Every year the population is increasing. The number of babies born is increasing. In line with that, one of the most important baby needs is baby diapers. Due to the human desire for practical activities, the use of disposable baby diapers has also increased. Based on this, the need for disposable baby diapers has also increased. This is a potential or potential market share for entrepreneurs or companies to produce baby diapers. Therefore, currently there are many choices of baby diapers available in the market. This has led to the emergence of competition among baby diaper manufacturers, including the Sweety brand Baby Diapers, both at the national level and in the Sulawesi Region. This study aims to examine the appropriate strategy carried out by Baby Diapers with the Sweety brand in distributing and marketing in the Sulawesi Region. In this study, the SWOT matrix analysis was used to analyze internal and external factors so that an appropriate strategy was obtained in distributing and marketing sweety baby diapers products. The results of the research resulted in alternative strategies: Maintain product quality, increase horizontal and vertical distribution, maintain program continuity, maintain competitive prices, improve human resource competence.